Leadership in Resorts: a study of styles practiced in Brazil - Giuliani, Thaís de Almeida; Oliva, Eduardo de Camargo (Revista Turismo em Análise, 2014)
The hotel industry is deeply affected by the behavior of its leaders and their personal characteristics, and especially by the way the leader influences its followers to achieve the goal. Therefore, this paper has a general objective to identify and analyze the styles of leadership practiced in Brazilian resorts. In addition, this dissertation identified the group of managers, which possess the transactional and transformational leadership considering the opinion of the very managers and leaders. Hence, as the approach for the research was carried out an exploratory descriptive study of qualitative and quantitative nature, it included 169 staff members of 14 resorts certified by the Brazilian Association of Resorts of Brazil of all the regions of the country. The data collected through the quantitative research were treated by means of the statistical technique of confirmatory factor analysis, as well as statistical techniques of frequency analysis and variance. The data obtained through the qualitative research were analyzed by means of the technical analysis of speech - Focus Group. The results of the quantitative research showed that the predominant leadership style practiced in Brazilian resort is the Transformational. In the other hand, the results of the qualitative research presented itself the opposite and showed that the predominant leadership style is Transacional, besides showing difference in opinion within the professionals researched, considering the genre. This discrepancy between the results of two surveys led to the search for a greater understanding of the possible causes, reaching the conclusion that social desirability may explain the difference of opinion leaders and participants of the quantitative research.